Final deadline for candiates to submit materials for voter guide (1976)
This notice announces a final deadline for candidates to submit materials for inclusion in the voter guide We The People. Candidates are required to provide a black-and-white photograph and a 100-word platform statement by 3:00 p.m. on July 31. The guide is described as a free publication distributed to hundreds of thousands of California voters, and organizers urge prompt submission due to printing deadlines. Contact information is provided for John Paul Clay of American Outlook in Altadena.